Differential Diagnosis of Cardiac Amyloidosis and Hypertrophic Cardiomyopathy - M. S. Bychkova; E. V. Reznik; D. V. Ustyuzhanin; G. N. Golukhov (SINAPS LLC, 2023)
Diagnosis and differential diagnosis of cardiac amyloidosis and hypertrophic cardiomyopathy is difficult in some cases, which is confirmed by the presented clinical observation. The patient A., 67 years old, from the age of 59 for 7 years suffered from arterial hypertension with a maximum blood pressure of 170/100 mmHg, received hypotensive therapy. Myocardial infarction, a history of stroke denies. Since January 2018, at the age of 65, against the background of spontaneous stabilization of blood pressure figures, shortness of breath when climbing to the 2nd floor, lifting weights, suffocation at night, swelling of the shins, feet, in connection with which I turned to a doctor. When examined on an electrocardiogram, a low voltage of QRS complexes in the leads from the extremities was noted, there was no increase in the amplitude of the r wave in V1-3. Echocardiography revealed a thickening of the interventricular septum and the posterior wall of the left ventricle up to 1.9 cm without obstruction of the outlet of the left ventricle, restrictive type of diastolic dysfunction, dilation of the left and right atria, moderate pulmonary hypertension, moderate amount of fluid in the pericardial cavity. Magnetic resonance imaging of the heart revealed a pattern typical of cardiac amyloidosis: diffuse subendocardial contrast of the myocardium of both ventricles in the absence of local contractility disorders, increased myocardial thickness in all segments, hydropericardium. Biopsy of the skin and subcutaneous fat with Congo red staining and polarization microscopy revealed no amyloid deposits. No mutations in the transthyretin gene responsible for transthyretin amyloidosis (ATTR-amyloidosis) were detected during the genetic study. Sequencing of 10 genes encoding myocardial sarcomeric proteins in the MYBPC3 gene revealed a mutation c.3197C >G (p.Pro1066Arg) in a heterozygous state, previously described in patients with hypertrophic cardiomyopathy of Slavic origin. Cascade family screening for the mutation was not carried out due to the fact that the patient did not know the father, the mother died at the age of 75 from heart failure, the only son died from an accident six months before the patient's treatment. On 15.02.2019, the patient suffered a circulatory arrest with successful resuscitation measures. For the purpose of secondary prevention of sudden cardiac death, a single-chamber cardioverter-defibrillator was implanted on 22.02.2019. Despite the ongoing therapy, the patient died in March 2019. from progressive heart failure. Thus, a clinical case is presented where magnetic resonance imaging suspected amyloid cardiomyopathy, which did not receive morphological confirmation in biopsies of extra-cardiac localization. Hypertrophic cardiomyopathy caused by mutation c.3197C >G (p.Pro1066Arg) in the MYBPC3 gene was confirmed on the basis of clinical and instrumental and molecular genetic methods. The pattern characteristic of cardiac amyloidosis described in this patient with instrumental examination methods may be due to a violation of autophagy processes previously described with a number of mutations in the MYBPC3 gene, which may lead to the accumulation of amyloid-like inclusions in cardiomyocytes. For differential diagnosis of cardiomyopathies in complex cases, endomyocardial biopsy may be required. The possibility of coexistence of genetically determined hypertrophic cardiomyopathy and amyloid heart disease is not excluded.